MUSIC CUED EXERCISES FOR PEOPLE LIVING WITH DEMENTIA: A SYSTEMATIC REVIEW (International Journal of Physiotherapy, 2018)
Background: Dementia can be associated with motor and non-motor disorders such as cognitive impairment, depression, and behavioral disturbance. The symptoms typically progress gradually over time. Music-cued exercises have been of therapeutic interest in recent years, especially to enable people with chronic neurological diseases to move more easily and to experience greater well-being. Objective: To investigate whether music-cued exercises are more effective than usual care for the management of motor and non-motor symptoms in people living with dementia.Methods: Systematic searching of the international literature was conducted in January 2018. Keywords were searched through electronic databases including MEDLINE, CINAHL, Embase, PsycINFO, PubMed, Scopus, the Web of Science, Science Direct, Wiley online library, and JOVE. The Cochrane collaboration tool was used to assess the risk of bias of the randomized controlled trials (RCTs). The Downs and Black checklist assessed the quality of non-RCTs.Results: Twelve studies met the eligibility criteria, including 4 RCTs. Three investigated the effects of music-cued exercises on motor performance, four examined non-motor outcomes, four quantified the level of exercise participation, and one examined both motor and non-motor outcomes. The included studies were of modest to low quality.Conclusion: There is growing evidence for the beneficial effects of music-cued exercises for people living with dementia. Enjoyable music and physical exercises matched to rhythmical music appear to have benefits for some individuals.The dosage of music-cued exercise is a key determinant of the motor and non-motor outcomes in people living with a variety of forms of dementia.